Investigating burn cases, knowledge, attitudes and practices to burn care and prevention in Ethiopia: a community-survey - Baye Denekew; Caitlin Hebron; Abeba Mekonnen; Mihret Ayele; Kassahun Negash; Muluken Desalegne; Patricia Price; Tom Potokar (Journal of Global Health Reports)
# Background